Acceleration self-compensation mechanism and experimental research on shock wave piezoelectric pressure sensor. (March 2021) - Wang, Guicong; Li, Yingjun; Cui, Huanyong; Yang, Xue; Yang, Cong; Chen, Naijian
Graphical abstract: Highlights: Measurement crystal with acceleration compensation principle is proposed. The shock wave piezoelectric pressure sensor with acceleration compensation is designed. Structural optimization design on acceleration compensation is carried out. The acceleration sensitivity of the sensor is greatly reduced. Natural frequency of piezoelectric pressure sensor exceeds 200 kHz. Abstract: This paper presents acceleration self-compensation mechanism and experimental research on shock wave piezoelectric pressure sensor, in order to eliminate the parasitic effect of acceleration on pressure measurement. Firstly, the demand analysis of the pressure sensor during the dynamic measurement of the explosion pressure field is completed. Aiming at the phenomenon of acceleration parasitic effect of piezoelectric pressure sensor, a structure of novel measurement crystal with acceleration compensation principle is proposed, and the mechanism of acceleration compensation is studied. The theoretical calculation formula of the piezoelectric sensor's acceleration sensitivity is derived, and the shock wave piezoelectric pressure sensor with acceleration compensation is designed. Two kinds of finite element simulation structural models without acceleration compensation and with acceleration compensation are established to compare their measurement performances. Structural optimization design of piezoelectric pressure sensor with acceleration compensation is carried out to eliminate the acceleration sensitivity. The calibration experiment of the piezoelectric pressure sensor is completed by building the calibration experiment platform. The experimental results show that the acceleration sensitivity of the sensor is greatly reduced, which are in good agreement with the theoretical derivation and simulation results. The sensor has superior dynamic characteristic, and its natural frequency exceeds 200 kHz. The research content of this paper has important theoretical significance and practical value for reducing the acceleration parasitic effect of piezoelectric pressure sensor.